Pengelolaan Bantuan Operasional Sekolah (BOS) di Era Digital dalam Meningkatkan Mutu Pendidikan di Sekolah Dasar Negeri 092/VII Pematang Kolim I Kecamatan Pelawan Kabupaten Sarolangun - Najma Najma; Tuti Indriyani; Sodiah Sodiah (SOKO GURU: Jurnal Ilmu Pendidikan, 2025)
Study This aim For Analyze management of aid funds Operational School in increase quality education at State Elementary School 092/VII Pematang Kolim I. Knowing effectiveness use applications used​ in do Management of BOS funds at State Elementary School 092/VII Pematang Kolim I. Describes the obstacles and difficulties experienced State Elementary School 092/VII Pematang Kolim I in manage aid funds Operational School . Research This use type study descriptive qualitative . Focusing on the management of aid funds operational school in increase Quality of Education at State Elementary School 092/VII Pematang Kolim I. Based on results observations conducted by researchers at State Elementary School 092 /VII Pematang Kolim I, found Not yet effective in operational fund management school (BOS). Data collection techniques with using interview , observation and documentation techniques . As for qualitative data analysis with do data reduction , data presentation and drawing conclusions. Findings study Management of Aid Funds Operational School at school state foundation 092/VII Pematang Kolim 1 has implemented with well , with carry out preparation of RKJS, RKT, determination budget school , determination allocation of funds and carrying out reporting . Use application in management of aid funds operational school is very effective , efficient , more save cost , right target , more practical , accountable , transparent and more easy implemented . Obstacles encountered in implementation often plans that have been set No in accordance with existing budget​ planned finance budget school , lack of power expert . As the solution adapt plan with condition real finance as well as stage training source Power reliable human being